Long-term trends in specialized outpatient health care utilization: an analysis in the context of a primary health care reform - Hannes Kohnke; Andrzej Zielinski; Anders Beckman; Henrik Ohlsson (BMC Health Services Research)
Abstract Background As primary health care forms the basis of the health care system, it is regarded as an efficient way to address main causes of, and risk factors for, poor health. In the Swedish health care system, general practitioners play a role in facilitating access to specialized health care and in coordinating care from other parts of the health care system. In Sweden, recent marketization efforts in primary health care, particularly the Patient Choice Reform, have adversely impacted geographical equity in access health care. This study aimed to examine long-term trends in specialized outpatient health care utilization in the context of the Patient Choice Reform, and to do so in regard to demographical, socioeconomic and geographical determinants of health care utilization. Method Register data from Region Skåne, the third most populous region in Sweden, was retrieved and a cohort was constructed, describing individuals’ health care utilization between 2007 and 2017. Utilization was measured as the number of outpatient visits to physicians in specialized health care, and based on trajectory analyses trends in utilization were identified. Differences in demographic, geographic and socioeconomic determinants between subgroups with distinct utilization trends were analyzed using logistic regression models. Results A closed cohort of 659,298 individuals was constructed. Utilization increased in all sex and age groups except for younger women where utilization decreased. Increased utilization was, in younger individuals, associated with lower socioeconomic status and, in older individuals, with higher socioeconomic status. In all female groups, increased utilization was associated with residence in urban areas and decreased utilization to residence in non-urban areas. Conclusion This study provides key insights into long-term trends in outpatient SHC utilization during a time period that overlaps with the Patient Choice Reform. The impact of socioeconomic and geographic determinants on utilization varies in magnitude and direction between different age groups of the population in a similar pattern as previously described for primary health care. However, unlike previously reported trends of primary health care utilization, specialized health care utilization in younger women is decreasing.